2016
DOI: 10.3390/nu8040224
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Nutrition between Cambodian Women over the Last 15 Years (2000–2014)

Abstract: This study aimed to describe the trends over four nationally representative Demographic Health Surveys (2000, 2005, 2010, and 2014) of the nutritional status of women of reproductive age in Cambodia and to assess the main factors of inequality with regards to nutrition. The prevalence of undernutrition and over-nutrition evolved in opposite trends from 2000 to 2014, with a significant decrease in underweight and a significant increase in overweight women. This results in a shift, with overweight prevalence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The 21 studies included in this review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] include data from 38 countries from Asia, Africa and Latin America ( Figure 3 ), and assess trends in anemia among WRA between 1990 and 2017. The characteristics and quality appraisal scores of the included studies, as well as the observed annualized reduction in WRA anemia, are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 21 studies included in this review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] include data from 38 countries from Asia, Africa and Latin America ( Figure 3 ), and assess trends in anemia among WRA between 1990 and 2017. The characteristics and quality appraisal scores of the included studies, as well as the observed annualized reduction in WRA anemia, are presented in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The median methodological quality score was 7 (range: 5.5–8), resulting in eight studies classified as low quality, eight studies [ 19 , 24 , 27 , 29 , 30 , 32 , 34 , 36 ] classified as moderate, and five studies [ 20 , 28 , 33 , 38 , 39 ] classified as high quality. Reduction in WRA anemia varied widely across the included studies, with CAGR ranging from −0.4 to −13.0%, with a median of −3.8%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this type of context, anemia reduction programs may also need to prioritize strategies that reduce nonnutritional causes of anemia. We use published information on Bangladesh and Cambodia, two countries that have recent relevant data on anemia etiology and program effectiveness to reduce anemia, as examples of how different data may help inform and understand the anemia public health response and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Karakochuk et al . reported IDA prevalence 10 times higher among women with Hb disorders, compared with those without Hb disorders in a rural province of Cambodia, but nationally representative analyses suggest that anemia could not be explained by nutritional deficiencies or Hb disorders . Based on the national ID prevalence (<7% regardless of inflammation‐adjustment), national iron delivery interventions are likely not needed .…”
Section: Discussionmentioning
confidence: 99%